The impact of brand awareness on brand image: the case of mobile phone market in vavuniya district - Sinthupa, N.; Karunanithy, M. (University of Jaffna, 2022)
Purpose: The purpose of this study is to explore how brand awareness influence in forming strong brand image in Vavuniya District mobile phone Market. Through this brand managers can get an idea of how to design and implement their marketing campaigns and strategies to enhance brand awareness and how to establish strong brand image through brand awareness in the market place. Methodology: Population relevant for this study is the individuals in Vavuniya District who use mobile phone. Since it is difficult to collect data from all the mobile phone users in the Vavuniya District researcher has selected Vavuniya district to conduct his research. Further, it is convenience for researcher to collect data from the Vavuniya. The sample of this study is consist 250 respondents taken from the population who live in Vavuniya district. Researcher select Vavuniya since it is convenient and easy to access respondents by researcher. A structured questionnaire has been employed to collect primary data from respondents. Data was collected directly from sample element by distributing the questionnaire forms. Findings: Through the analysis it is clear that there is significant influence of brand awareness (Brand recall and Brand recognition) on the brand image in Vavuniya District mobile phone industry. Also model Summery be concluded that 28.4% variations of Brand Image explained by Brand Awareness. The researcher can conclude that Brand awareness have an impact on the brand image in the Vavuniya District Mobile phone industry. In this study, the relationship between the brand awareness and brand image were found. P value 0 <0.05 (significance level) for both brand awareness and brand image, Therefore we do not reject H2. Therefore researcher can conclude that there is a relationship between Brand Awareness and Brand Image in Vavuniya District mobile phone Market. Research Limitations: The sample is a convenience sample therefore it is difficult to generalize to a larger audience. Due to the practical difficulties it is hard to gather information from a considerable portion of population. Also, as per the test results all the R square value is less than 70% and it is relatively low level. It is mean that there are other factors also influencing Brand image & Brand awareness except the above discussed factors. Implications: According to the demographical factors it is clear that it is important to identify the target market for the mobile phone with this range to fulfill expectations of customers and to deliver maximum value for the customer. According to Findings we can conclude that respondent have brand awareness and the Image are high mobile phone brands in mobile phone Market in Vavuniya District. Among the Mobile Phone brands in Vavuniya District Samsung, Nokia, Huawei, HTC, OPPO, Vivo and Apple are the leading brands who cater mobile devices for the Province. However, each brand has the unique identity in terms of how they address the target market, there for this research will provide information for them to identify the dynamic nature of the customer behaviors towards brand awareness & Brand image, after all this give their choice if the brand for their need of mobile device.
Keywords: Brand; Brand awareness; Brand image; Brand associations; Brand attitude; Brand personality; Mobile phone market